Perancangan Sistem Informasi Nomor Antrean untuk Meningkatkan Efisiensi Layanan di SAMSAT Banyuasin - Arnando, Ferdi; Ubaidillah, Ubaidillah (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
Managing motor vehicle administration and taxation in Indonesia, mainly through the One-Stop Integrated Administration System (SAMSAT), is crucial for enhancing public services. SAMSAT Banyuasin, as part of the government institution responsible for vehicle administration and taxation, faces challenges in service efficiency due to the continued use of a manual queuing system. This article aims to develop a Queue Number Information System to improve the structure, transparency, and user experience at SAMSAT Banyuasin. The literature review indicates that previous research has successfully optimized queuing systems in various service contexts, such as in bank teller services. This approach provides a conceptual foundation for designing the Queue Number Information System at SAMSAT Banyuasin. The research methodology involves collecting primary and qualitative data through direct observation and interviews. The design phase utilizes the Waterfall model, encompassing requirement analysis, system design (using UML), implementation, testing, and maintenance. Results and discussions include details about implemented features, such as the login interface, registration dashboard, queue number call/monitor dashboard, print report dashboard, and settings/configuration dashboard. The implementation process, testing, and maintenance are also explained. With this design, it is anticipated that the Queue Number Information System can be an effective solution to enhance service efficiency at SAMSAT Banyuasin. Implementing this technology will optimize administrative processes, reduce customer waiting times, and improve public satisfaction.